2013
DOI: 10.1039/c2ra23171a
|View full text |Cite
|
Sign up to set email alerts
|

Porous cesium impregnated MgO (Cs–MgO) nanoflakes with excellent catalytic activity for highly selective rapid synthesis of flavanone

Abstract: Magnesium oxide (MgO) is an excellent base catalyst and its performance is well controlled by its morphology, surface area and surface structures. Here, a simple methodology for the synthesis of porous cesium impregnated MgO (Cs-MgO) nano flakes, with enhanced surface area (156 m 2 g 21 ), basic properties and improved catalytic activity for flavanone synthesis, is presented. The synthesis of Cs-MgO nano flakes is performed through impregnation of CsNO 3 on a nesquehonite [Mg(HCO 3 )OH?2H 2 O] rod, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…[205][206][207] However, it is hard to build strongly basic sites on mesoporous silica through direct modification with alkali metal oxides. Dualcoating strategy.…”
Section: Post-synthetic Modificationmentioning
confidence: 99%
“…[205][206][207] However, it is hard to build strongly basic sites on mesoporous silica through direct modification with alkali metal oxides. Dualcoating strategy.…”
Section: Post-synthetic Modificationmentioning
confidence: 99%
“…In addition, we compared the catalytic performance of [TMG] with the results of other catalysts in the previous literatures [18][19][20][21][22][23][24][25] (Table 2). It was found that over-high temperature and too long reaction time were often taken to achieve a moderate catalytic performance.…”
Section: Catalyst Selectionmentioning
confidence: 98%
“…It can be seen that the M2 selectivity and Si conversion of Cu-p is 5.7 and 1.6%, respectively, while that of Cu-f increases to 54.0 and 16.3%, respectively. This is because the ake structure and higher surface area of Cu-f offer better contact between the catalysts and the Si powders, 11 which can improve the catalytic property. For Cu-Cu 2 O-f, the M2 selectivity and Si conversion rises up to 62.5 and 24.8%, respectively, and more importantly, Cu-Cu 2 O-CuO-f shows much increased values of 82.0 and 32.4% in the rst test (its values are reproducible during 3 tests), respectively, higher than those of Cu 2 O-CuO-f (80.1% M2 selectivity and 30.7% Si conversion).…”
Section: Catalytic Propertymentioning
confidence: 99%
“…The aky metals such as Al, 1 Ni, 2 Zn, 3 Au, 4 Cu, 5,6 and alloys, 7,8 which are generally produced by ball milling in industry, 1 are widely applied in electrode material, 5,9 pigments, 3,10 and catalysts. 11 This is because of their two-dimension structural characteristics, which endow these materials with some special properties, such as good adhesive ability, 10,12 excellent conductivity, 5,9 strong light reection 3,10 and commendable catalytic performance. 11,13 It is known that the catalytic performance of a heterogeneous catalyst is strongly affected by contact area between reactants and metal catalyst particles with a specic morphology and/or small particle size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation